Development, validation, and potential applications of the hepatitis C virus injection-risk knowledge scale (HCV-IRKS) among young opioid users in New York City. (1st January 2019) - Quinn, Kelly; Fong, Chunki; Guarino, Honoria; Mateu-Gelabert, Pedro
Highlights: A 5-item scale has excellent validity and reliability for measuring HCV knowledge. Mean percent correct among five drug-injection HCV transmission risk factors was 75%. Drug injectors and those testing HCV antibody-positive had highest knowledge levels. Abstract: Background: Hepatitis C virus (HCV) incidence has increased dramatically in the United States in recent years and is associated with the opioid epidemic due to high HCV transmission risk among people who inject drugs (PWID). HCV transmission knowledge is difficult to ascertain given the lack of psychometrically-tested measures. We developed and validated an HCV injection-risk knowledge scale. Methods: Analyses used data from 539 New York City opioid users ages 18-29 recruited via respondent-driven sampling in 2014–16. Blood samples yielded HCV antibody status. Principal components analysis (PCA) of nine knowledge items answered true, false, or don't know identified useful scale items. We evaluated internal consistency with the Cronbach's alpha coefficient and assessed construct validity by comparing knowledge levels with those from a previously validated general HCV knowledge scale and by comparing key sub-group knowledge levels. Results: PCA identified one component with five items that explained 45% of the total variance and had high internal consistency (alpha=0.91). All items referred to transmission through drug-injection equipment and practices: sharing cookers, cottons, diluting water, water containers, and cleaning syringes with water. The mean percent correct was 75%, and as expected, was moderately correlated with general HCV knowledge (Spearman's rho=0.55). As hypothesized, knowledge levels were highest for those previously tested for HCV, those with HCV antibody-positive status, PWID, and those who had received harm reduction information in various settings. Conclusions: The 5-item, validated HCV Injection-Risk Knowledge Scale (HCV-IRKS) may provide educators, care providers, and researchers with critical information for reducing HCV among PWID.